Wireless sensor networks : 11th China Wireless Sensor Network Conference, CWSN 2017, Tianjin, China, October 12-14, 2017, Revised selected papers /: 11th China Wireless Sensor Network Conference, CWSN 2017, Tianjin, China, October 12-14, 2017, Revised selected papers. (2018) - Unknown
No abstract available